واقع أساليب التقويم المستخدمة في التربية الخاصة - عازب أحمد, عبد المنعم; منصور, مصطفى (جامعة الوادي - University of Eloued, 2022)
تصنف أساليب التقويم في التربية الخاصة إلى أساليب مقننة وأخرى غير مقننة ,أما الأساليب المقننة فهي تلك الاختبارات التي تتميز يإجراءات مضبوطة في الإعداد والتطبيق والتصحيح وتقدير الدرجات وتفسير النتائج , كما يعبر عن أداء المفحوص في هذه الاختبارات بدرجات خام تحول إلى قيم معيارية حتى نتمكن من مقارنة أدائه بأداء أقرانه عمريا أو صفيا. أما الأساليب غير المقننة كالملاحظة والمقابلة ومقاييس التقدير والاختبارات التحصيلية وقوائم الشطب لها دور في جمع المعلومات , وتعتبر عاملا مساعدا للأساليب المقننة في اتخاذ القرارات الهامة عن أداء المفحوصين . وتهدف الورقة البحثية الحالية إلى التعرف على بعض أساليب التقويم المقننة, وستقتصر على الاختبارات المقننة لقياس القدرات العقلية مثل : مقياس ستانفورد بينيه ومقياس وكسلر لذكاء الأطفال , ومقياس جودانوف , ومقياس مكارثي للقدرة العقلية , ومقياس المفردات اللغوية المصورة , ومقياس الذكاء المصور لتقويم الكفاية العقلية ,سنتناول هذه المقاييس من حيث أغراضها واستخداماتها ومظاهر قوتها وضعفها والانتقادات الموجهة إليها. Abstract: The article aims to identify the assessment methods and tools used in special education, specifically in order to diagnose people with learning difficulties, whether developmental or academic. Where we relied on a sample of those tools represented in the famous intelligence tests in the educational community, which are: the StanfordBinet Scale, the Wechsler Scale for Children's Intelligence, the Godanov Scale, the McCarthy Mental Ability Scale, the Pictorial Vocabulary Scale, and the Pictorial Intelligence Scale for evaluating mental adequacy. Where we made an analytical comparison between those tests in terms of their function and the positive and negative points for each one. Despite the passage of decades and the absence of new tools, the research has found the effectiveness of these tools in diagnosing people with learning difficulties until advanced measures are reached that respond to the successive developments in various sciences and contribute to diagnosing the various cases of this category.
مقال
Keywords: التقويم ; أساليب التقويم المقننة; Diagnosis; IQ tests; People with learning disabilities